Avaliação da contribuição do revestimento na isolação sonora de paredes de alvenaria - Friedrich, Adriana Flores (2010)
The research presents the sound insulation in masonry walls coated with plaster. Three walls were built in laboratory, studied in specific tests. Measurements were carried out varying some components of the wall, such as the type of the block and the combinations of coarse mortar, plaster and stucco on the faces of the wall. The mortars used in the tests were industrialized and had an additive in their conglomerate that aimed to its structural and commercial improvement. Also, paints and textures were used alternately in the tests to verify the importance of this kind of coating on the sound transmission loss of the wall. The laboratory findings showed up the location of the coincidence frequency and the acoustic accomplishment of the coated masonry walls. Variation of these factors had a direct influence at the system hardness. The increase of the variation in the set caused by the addition of the mortar layers does vary, further of frequency of coincidence, the frequency of resonance wall thickness. It was still checked that three days of drying of the mortar was sufficient to have satisfactory results on the essays. The laboratory tests brought more agility with the evidence and the validation that the cure of the aggregate in the wall needs three days. Another important verification was the increase of 5 dB on the Weighted Noise Reduction Index (Rw) when the wall is coated in both faces. The using of paint and texture didn t contribute to the acoustic performance of the wall. Just, the utilization of texture shown a raise of acoustic performance of 1 dB on the Weighted Noise Reduction Index (Rw). That didn t happend with the duplication of the layer of plaster, that obtained acoustic insulation indicators lower than 1dB in the set.